Răspunsuri

2014-07-27T23:53:00+03:00
(a+b)-18=a-b

a-b= 1/4 *a

a-b=a/4   aducem la acelasi numitor

4a-4b=a

4a-a=4b

3a=4b

a=4b/3

(4b/3+b)-18= 4b/3 -b    aducem la acelasi numitor

4b+3b-54=4b-3b

7b-54=b

7b-b=54

6b=54

b=54:6

b=9

a=4b/3=  4*9/3=  4*3=12
2 3 2
2014-07-28T08:23:35+03:00
(x + y)  = (x - y) + 18
(x - y) = x * 1/4
-------
(x + y) - (x - y) = 18
x - x + y + y = 18
2y = 18
y = 18 / 2
y = 9

x - y = x / 4
x - x / 4 = y
x(1 - 1/4) = y
3x / 4 = y
3x / 4 = 9
x = 9 * 4 / 3
x = 36 / 3
x = 12